Conductive composite particles, method for producing the same, and electrode

Conductive complex particles formed from π-cooperative conductive polymers and polyanions, modified by a fourth-grade ammonium compound, address the challenge of small particle diameter requirements for high conductivity electrodes, enabling efficient and adjustable conductivity in electrode production.

JP7624906B2Active Publication Date: 2025-01-31SHIN ETSU POLYMER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021164111
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-05
Publication Date
2025-01-31
Estimated Expiration
2041-10-05

AI Technical Summary

Technical Problem

Existing technologies face challenges in producing conductive particles with small particle diameters suitable for high conductivity applications, as they often require substrate particles, limiting their effectiveness in forming electrodes.

Method used

The development of conductive complex particles composed of π-cooperative conductive polymers and polyanions, where some anion groups are modified by a fourth-grade ammonium compound, allowing for smaller particle sizes and adjustable conductivity through controlled particle diameters.

Benefits of technology

These particles enable the production of electrodes with enhanced conductivity by eliminating the need for substrate particles and allowing for precise adjustment of particle diameter, facilitating easier manufacturing and improved electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624906000001
    Figure 0007624906000001
Patent Text Reader

Abstract

To provide conductive composite body particles which do not require substrate particles and a production method thereof, and an electrode formed of the conductive composite body particles.SOLUTION: Provided is a production method of conductive composite body particles, comprising: a step of adding an aqueous dispersion of a conductive polymer containing a conductive composite body comprising a π-conjugated conductive polymer and a polyanion, and water to a reaction mixture containing a quaternary ammonium compound and an organic solvent to thereby react the quaternary ammonium compound and a part of anionic groups of the polyanion which the conductive composite body possesses and to precipitate a reaction product; a step of washing the reaction product with a washing liquid; a step of drying the washed reaction product; and a step of pulverizing the dried reaction product to thereby obtain conductive composite body particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to conductive composite particles containing a π-conjugated conductive polymer, a method for producing the same, and an electrode. [Background technology]

[0002] Conventionally, a filler may be added to a raw material composition of a resin molded product. Patent Document 1 discloses a technique of adding conductive particles, in which a conductive complex containing a π-conjugated conductive polymer and a polyanion is coated on the surface of a base particle, to the raw material composition. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-093377 Summary of the Invention [Problem to be solved by the invention]

[0004] In the technology of Patent Document 1, since the base particle is an essential component, it is difficult to obtain conductive particles smaller in particle size than the base particle. Although the base particle is useful in filler applications, for example, when forming an electrode with high conductivity, conductive particles with a small particle size are advantageous.

[0005] The present invention provides conductive composite particles that do not require a base particle, a method for producing the same, and an electrode formed from the conductive composite particles. [Means for solving the problem]

[0006] [1] A conductive composite particle comprising a conductive complex containing a π-conjugated conductive polymer and a polyanion, wherein a portion of the anion groups of the polyanion are modified by a reaction with a quaternary ammonium compound. [2] The conductive composite particle according to [1], wherein the monovalent organic group bonded to the nitrogen atom of the quaternary ammonium compound has 5 or more carbon atoms. [3] The conductive composite particle according to [2], wherein the organic group is a hydrocarbon group. [4] The conductive composite particle according to any one of [1] to [3], wherein the total number of carbon atoms in the quaternary ammonium compound is 40 or less. [5] The conductive composite particle according to any one of [1] to [4], wherein the quaternary ammonium compound includes at least one compound arbitrarily selected from the group consisting of tetrabutylammonium, tetraoctylammonium, and tetradecylammonium. [6] The conductive composite particles according to any one of [1] to [5], which have an average particle size of 500 μm or less. [7] The conductive composite particle according to any one of [1] to [6], wherein the π-conjugated conductive polymer contains poly(3,4-ethylenedioxythiophene) or the polyanion contains polystyrenesulfonic acid. [8] An electrode comprising the conductive composite particle according to any one of [1] to [7]. [9] A method for producing conductive composite particles, comprising: a step of adding a conductive polymer aqueous dispersion containing a conductive complex containing a π-conjugated conductive polymer and a polyanion, and water to a reaction solution containing a quaternary ammonium compound and an organic solvent, thereby reacting the quaternary ammonium compound with a part of the anion groups of the polyanion in the conductive complex, and precipitating a reaction product; a step of washing the reaction product with a washing solution; a step of drying the washed reaction product; and a step of pulverizing the dried reaction product to obtain conductive composite particles.

[10] The method for producing conductive composite particles according to [9], wherein the quaternary ammonium compound contains a quaternary ammonium halide. Effect of the Invention

[0007] The conductive composite particles of the present invention do not require a base particle, and can be milled to a desired particle size. In the electrode of the present invention, the electrical conductivity of the electrode can be adjusted by adjusting the particle size of the conductive composite particles contained therein. According to the method for producing the conductive composite particles of the present invention, the above-mentioned excellent conductive composite particles can be easily produced.

[0008] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range.

[0010] ≪Conductive composite particles≫ A first aspect of the present invention is a conductive composite particle comprising a conductive composite containing a π-conjugated conductive polymer and a polyanion, some of the anion groups of which have been modified by a reaction with a quaternary ammonium compound. The conductive composite particles of this embodiment are an aggregate of particles (powder).

[0011] The average particle size of the conductive composite particles of this embodiment is preferably 500 μm or less, more preferably 300 μm or less, and even more preferably 150 μm or less, from the viewpoint of improving the electrical conductivity by increasing the number of particles in a unit volume (density) and increasing the contact area between particles. The above average particle size was determined as a particle size at which the cumulative frequency of the particle size distribution measured by a laser diffraction particle size distribution analyzer was 50% in terms of volume percentage.

[0012] The electrical conductivity (unit: S / cm) of the conductive composite particles of this embodiment is preferably 1.0 or more, more preferably 3.0 or more, and even more preferably 5.0 or more. A higher electrical conductivity is preferable since it increases the electrical conductivity of the conductive composite particles. There is no particular upper limit to the electrical conductivity, and an example of the upper limit is 100 or less. The electrical conductivity of the conductive composite particles of this embodiment can be measured using a molded product obtained by compressing the conductive composite particles as a sample.

[0013] The conductive composite particles of this embodiment may contain water, but the smaller the water content, the more preferable. The water content relative to the total mass of the conductive composite particles is, for example, preferably 20 mass % or less, more preferably 10 mass % or less, and even more preferably 5 mass % or less. The water content is most preferably substantially 0 mass %. When the content is equal to or less than the upper limit of the above range, aggregation of the conductive composite particles can be suppressed when mixed with a non-aqueous material, for example, a binder component. The water content in the conductive composite particles is a value measured by the Karl Fischer method.

[0014] [Conductive composite] The conductive complex forming the conductive composite particle of this embodiment contains a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. In the polyanion, only a part of the anionic groups is doped into the π-conjugated conductive polymer, and there are excess anionic groups that are not involved in the doping. Since the excess anionic groups are hydrophilic groups, the conductive composite in which the excess anionic groups are not modified has water dispersibility.

[0015] (π-conjugated conductive polymer) The π-conjugated conductive polymer may be an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.

[0016] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable because of its excellent conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.

[0017] (Polyanion) A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity. The polyanions may be used alone or in combination of two or more kinds. The mass average molecular weight of the polyanion is preferably from 20,000 to 1,000,000, and more preferably from 100,000 to 500,000. The mass average molecular weight is the average molecular weight based on mass measured by gel filtration chromatography and calculated in terms of pullulan.

[0018] When the number of all anionic groups in the polyanion is taken as 100 mol %, the excess anionic groups are preferably from 30 mol % to 90 mol %, more preferably from 45 mol % to 75 mol %.

[0019] The excess anionic groups of the polyanion of the present invention that are not involved in the dope (hereinafter also referred to as "a portion of the anionic groups") are modified by reaction with a quaternary ammonium compound.

[0020] Since the conductive composite particles of this embodiment can be easily produced by the method described later, the quaternary ammonium compound preferably has four monovalent organic groups bonded to a nitrogen atom. The number of carbon atoms in each organic group is preferably 3 or more, more preferably 5 or more, and even more preferably 7 or more. The upper limit of the number of carbon atoms in each organic group is not particularly limited, and taking into consideration the solubility and reactivity in the reaction solution, it is preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less. The total number of carbon atoms in the organic groups contained in the quaternary ammonium compound is preferably 8-48, more preferably 12-44, and even more preferably 16-40. The number of carbon atoms in each organic group may be the same or different.

[0021] From the viewpoint of increasing the electrical conductivity of the conductive composite particle of this embodiment, each organic group particularly preferably has 4 to 10 carbon atoms, and most preferably has 5 to 8 carbon atoms.

[0022] The polyanion of the present invention preferably has the following substituent (C) formed by the reaction of a quaternary ammonium compound with a portion of the anionic group.

[0023] (Substituent C) -N + R 11 R 12 R 13 R 14 (C) [In formula (C), R 11 ~R 14 each independently represents a hydrocarbon group which may have a substituent.

[0024] In the substituent (C), the bond at the left end represents the bond between the negative charge of the anion group and the positive charge of the quaternary ammonium cation. Examples of an anion group that can be negatively charged include "-SO3 - " is an anionic group in which an active proton is bonded to an oxygen atom.

[0025] R in chemical formula (C) 11 ~R 14R in chemical formula (C) is a hydrocarbon group which may have a substituent. 11 ~R 14 is a substituent derived from a quaternary ammonium compound. Examples of the hydrocarbon group in chemical formula (C) include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. Examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the substituent on the aliphatic hydrocarbon group include a phenyl group and a hydroxyl group. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Examples of the substituent on the aromatic hydrocarbon group include an alkyl group having 1 to 5 carbon atoms and a hydroxyl group.

[0026] The quaternary ammonium compound is preferably water-insoluble, where water-insoluble means that the solubility in 100 g of water at 20° C. is less than 1 g. The water-insoluble quaternary ammonium compound has high reactivity with polyanions in the reaction liquid described below, and therefore can easily form the desired substituent (C).

[0027] The quaternary ammonium compound is preferably a tetraalkylammonium halide, because it has high reactivity with polyanions, and the reaction product is difficult to dissolve in the aqueous dispersion medium and easily precipitates. As the halogen ion of the counter anion, a bromide ion or a chloride ion is preferable, and a chloride ion is more preferable from the viewpoint of increasing the electrical conductivity.

[0028] Specific examples of the quaternary ammonium compound include quaternary ammonium salts such as tetraethylammonium salt, tetrapropylammonium salt, tetrabutylammonium salt, tetraoctylammonium salt, tetradecylammonium salt, tetraphenylammonium salt, tetrabenzylammonium salt, tetranaphthylammonium salt, etc. The alkyl groups constituting these quaternary ammonium compounds may be linear or branched. Examples of the counter anion of the ammonium cation include halogen ions such as bromide ion and chloride ion, and hydroxy ion.

[0029] The content of the polyanion in the conductive complex is preferably 1 part by mass or more and 1000 parts by mass or less, more preferably 10 parts by mass or more and 700 parts by mass or less, and even more preferably 100 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content of the polyanion is equal to or more than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or less than the upper limit, the amount of anion groups not involved in doping is appropriately suppressed, and the anion groups can be easily converted to hydrophobicity when reacting with a quaternary ammonium compound.

[0030] <<Conductive particle composition>> A second aspect of the present invention is a conductive particle composition (hereinafter, sometimes simply referred to as a composition) containing the conductive composite particle of the first aspect and other components, such as a binder component, a conductive assistant, an additive, a dispersion medium, etc.

[0031] [Binder components] The binder component is a resin other than the π-conjugated conductive polymer and the polyanion, or a precursor thereof. The precursor is a curable monomer or oligomer. The resin becomes the binder resin as it is, and the resin formed by curing the curable monomer or oligomer becomes the binder resin. The binder component contained in the composition of this embodiment may be one type or two or more types.

[0032] Examples of the resin include binder resins that are added to electrode active materials of known lithium ion secondary batteries, such as fluorine-containing resins, polyolefins, conjugated diene polymers, acrylic resins, polyvinyl alcohol resins, cellulose resins, latexes, and other resins.

[0033] Examples of fluorine-containing resins include polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer. Examples of polyolefins include polyethylene, polypropylene, ethylene propylene rubber, and modified products thereof. Examples of the conjugated diene polymer include styrene-butadiene copolymers and hydrogenated products thereof, acrylonitrile-butadiene copolymers and hydrogenated products thereof, and acrylonitrile-butadiene-styrene copolymers and hydrogenated products thereof. Examples of the acrylic resin include a methacrylic acid ester-acrylate ester copolymer, a styrene-acrylate ester copolymer, and an acrylonitrile-acrylate ester copolymer. Examples of polyvinyl alcohol-based resins include polyvinyl alcohol and polyvinyl acetate. Examples of the cellulose-based resin include ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose. Examples of the latexes include styrene-butadiene latexes, acrylic latexes, acrylonitrile-butadiene latexes, fluorine-based latexes, and silicone-based latexes.

[0034] The content of the binder component in the composition of this embodiment is, for example, 10 parts by mass or more and 10,000 parts by mass or less per 100 parts by mass of the conductive composite particles.

[0035] [Conductive additive] Examples of the conductive assistant include known conductive assistants added to electrode active materials of lithium ion secondary batteries, such as carbon materials and metal particles. Examples of the carbon material include carbon black, graphite, vapor-grown carbon fiber, carbon nanofiber, and carbon nanotube. Examples of the metal particles include silver particles, copper particles, gold particles, and aluminum particles. The conductive assistant included in this embodiment may be of one type or of two or more types.

[0036] The content of the conductive assistant in the composition of this embodiment is, for example, 0.1 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the conductive composite particles.

[0037] [Additives] Examples of additives include inorganic compounds (excluding carbon materials and metal particles). Examples of inorganic compounds include silica, silica-alumina, glass, calcium carbonate, calcium hydroxide, talc, alumina, titania, zirconia, magnesium hydroxide, aluminum hydroxide, hydrotalcite, and mica.

[0038] The content of the additive in the composition of this embodiment is, for example, 0.1 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the conductive composite particles.

[0039] [Dispersion medium] The composition of this embodiment may contain a dispersion medium for dilution. The dispersion medium may be any of water, an organic solvent, and a mixture of water and an organic solvent.

[0040] Examples of the organic solvent include alcohol-based solvents (alcohols), ether-based solvents, ketone-based solvents, and nitrogen atom-containing solvents. Examples of alcohol-based solvents include methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 2-methyl-2-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol, allyl alcohol, ethylene glycol, propylene glycol, propylene glycol monomethyl ether, and ethylene glycol monomethyl ether. Examples of the ether solvent include diethyl ether, dimethyl ether, propylene glycol dialkyl ether, and diethylene glycol diethyl ether. Examples of the ketone solvent include diethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl amyl ketone, diisopropyl ketone, methyl ethyl ketone, acetone, and diacetone alcohol. Examples of the nitrogen atom-containing solvent include N-methylpyrrolidone, dimethylacetamide, and dimethylformamide. The organic solvent contained in the composition of this embodiment may be one type, or two or more types.

[0041] The content of the dispersion medium relative to the total mass of the composition of this embodiment is, for example, from 10% by mass to 90% by mass.

[0042] ≪Electrode≫ A third aspect of the present invention is an electrode comprising the conductive composite particles of the first aspect. The shape of the electrode is not particularly limited, and examples thereof include known electrode shapes such as a plate, sheet, film, rod, column, and the like. The average thickness of the plate-, sheet- or film-like electrodes is, for example, preferably 0.01 μm or more and 1000 μm or less, and more preferably 0.1 μm or more and 100 μm or less, from the viewpoint of achieving both a reduction in electrical resistance and a thin electrode. The average thickness of a plate-, sheet-, or film-like electrode is the average value of the thickness measurements taken at 10 or more randomly selected points on the cross section of the electrode observed using a magnifying observation means such as a measuring microscope. The electrode of this embodiment may be supported by a base material such as a film or substrate, or may be an independent electrode. When the electrode of this embodiment is used as an electrode for a lithium ion secondary battery, it may be either a positive electrode or a negative electrode.

[0043] The content of the conductive composite particles relative to the total mass of the electrode of this embodiment can be, for example, 50 mass % or more, 70 mass % or more, or 90 mass % or more, with the upper limit of the content being 100 mass %. The electrode of this embodiment may contain one or more components (other components) other than the conductive composite particles explained in the second embodiment.

[0044] <Electrode manufacturing method> Examples of methods for producing the electrode of this embodiment include a method of molding the conductive composite particles of the first embodiment or the conductive particle composition of the second embodiment into an electrode of a desired shape, and a method of applying the conductive particle composition of the second embodiment to a desired substrate and drying it to form an electrode layer (conductive layer) containing the conductive composite particles of the first embodiment on the surface of the substrate. The above molding method is not particularly limited, and examples thereof include press molding using a mold, extrusion molding using a die, etc. Examples of press molding include a method in which the conductive composite particles of the first embodiment are filled into a mold and pressed to form an electrode having a three-dimensional shape that reflects the shape of the mold. The substrate to which the composition is applied may be, for example, a substrate supporting an electrode active material layer of a known lithium ion secondary battery.Specific examples include metal materials such as copper foil, aluminum foil, and stainless steel plate.Also, a known resin film or resin plate may be used as the substrate.The coating method is not particularly limited, and a conventional method may be used.

[0045] <Battery> It is also possible to manufacture a battery or a capacitor equipped with the electrode of this embodiment. The battery may be a primary battery or a secondary battery. The form of the battery is not particularly limited, and examples thereof include known battery forms such as dry batteries, electrode-stacked laminate batteries, and button batteries. The battery has a positive electrode, a negative electrode, and an electrolyte. The electrode of this embodiment may be a positive electrode or a negative electrode.

[0046] <Method for producing conductive composite particles> A fourth aspect of the present invention is a method for producing conductive composite particles, comprising a reactive precipitation step, a washing step, a drying step, and a pulverization step. The reactive precipitation process is a process in which a conductive polymer aqueous dispersion containing a conductive complex containing a π-conjugated conductive polymer and a polyanion, and water is added to a reaction liquid containing a quaternary ammonium compound and an organic solvent, thereby reacting the quaternary ammonium compound with a portion of the anion groups of the polyanion in the conductive complex, and precipitating a reaction product. The washing step is a step of washing the reaction product with a washing liquid. The drying step is a step of drying the washed reaction product. The pulverization step is a step in which the dried reaction product is pulverized to obtain conductive composite particles.

[0047] [Reaction precipitation process] This process is a process in which a conductive polymer aqueous dispersion is added to an organic solution (reaction liquid) containing a quaternary ammonium compound, thereby precipitating a reaction product between the conductive complex and the quaternary ammonium compound in the reaction liquid.

[0048] When the conductive polymer aqueous dispersion is added to the reaction solution, the quaternary ammonium compound reacts stably with some of the anion groups of the polyanion of the conductive complex, which makes the conductive complex hydrophobic, making it difficult to stably disperse the conductive complex in the reaction solution, and the conductive complex precipitates to form a precipitate.

[0049] The organic solvent contained in the reaction liquid may be one type or two or more types. Examples of the organic solvent include methanol, ethanol, 1-propanol, isopropyl alcohol, n-butanol, t-butanol, and allyl alcohol.

[0050] The content of the quaternary ammonium compound in the reaction liquid is preferably 10 parts by mass or more and 5,000 parts by mass or less, more preferably 100 parts by mass or more and 1,000 parts by mass or less, and even more preferably 150 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the total mass of the conductive complex added. When the content is at least the lower limit of the above range, the reaction efficiency between the conductive complex and the quaternary ammonium compound is increased, and the reaction product can be easily obtained. When the content is equal to or less than the upper limit of the above range, a decrease in the conductivity of the conductive composite due to contamination with unreacted quaternary ammonium compound can be prevented.

[0051] The conductive polymer aqueous dispersion is a dispersion in which a conductive complex containing a π-conjugated conductive polymer and a polyanion is contained in an aqueous dispersion medium. Here, the aqueous dispersion medium is water or a mixture of water and a water-soluble organic solvent. The water-soluble organic solvent is one that dissolves in an amount of 1 g or more per 100 g of water (20° C.). Examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The aqueous dispersion medium may contain one type of water-soluble organic solvent, or two or more types of water-soluble organic solvents. The content of water relative to the total mass of the aqueous dispersion medium is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 80% by mass or more, and may be 100% by mass. When the content of water is large, the dispersibility of the conductive composite is increased, and the reaction efficiency with the quaternary ammonium compound is increased. Furthermore, the reaction product is easily precipitated in the reaction liquid.

[0052] The conductive polymer aqueous dispersion can be obtained, for example, by chemically oxidizing a monomer that forms a π-conjugated conductive polymer in an aqueous solution of a polyanion. Alternatively, a commercially available conductive polymer aqueous dispersion can be used. The chemical oxidation polymerization can use a known catalyst and oxidizing agent. Examples of the catalyst include transition metal compounds such as ferric chloride, ferric sulfate, ferric nitrate, and cupric chloride. Examples of the oxidizing agent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate.

[0053] The content of the π-conjugated conductive polymer and the polyanion relative to the total mass of the aqueous conductive polymer dispersion is preferably from 0.1% by mass to 5% by mass, more preferably from 0.5% by mass to 2% by mass, and even more preferably from 0.8% by mass to 1.5% by mass. When the content is within the above preferred range, the dispersibility of the π-conjugated conductive polymer and the polyanion is improved, and the reaction efficiency with the quaternary ammonium compound is increased.

[0054] The volume ratio (V1 / V2) of the volume V2 of the conductive polymer aqueous dispersion to be added to the volume V1 of the reaction liquid is preferably from 0.3 to 3.0, more preferably from 0.5 to 2.5, and even more preferably from 0.8 to 2.0. When the temperature is within the above preferred range, the reaction proceeds stably and the reaction product precipitates easily.

[0055] The method of adding the conductive polymer aqueous dispersion to the reaction liquid is not particularly limited, and a desired amount may be added all at once in a few seconds, or may be added slowly dropwise. From the viewpoint of obtaining a conductive composite having a small average particle size and increasing the conductivity, the method of adding slowly dropwise is preferred. The rate at which the conductive polymer aqueous dispersion is dropped into the reaction liquid is preferably 1 minute to 3 hours, more preferably 10 minutes to 2 hours, from the start to the end of the drop, assuming that a constant amount is continuously dropped. During the drop, it is preferable to gently stir the reaction liquid. When the temperature is within the above preferred range, the reaction proceeds stably and the reaction product precipitates easily.

[0056] The amount of the conductive polymer aqueous dispersion added dropwise to the reaction liquid is preferably 0.1 to 100 ml / min, and more preferably 1 to 10 ml / min. During the dropwise addition, it is preferable to gently stir the reaction liquid. When the temperature is within the above preferred range, the reaction proceeds stably and the reaction product precipitates easily.

[0057] When the conductive polymer dispersion is added to the reaction liquid and gently stirred, a reaction product precipitates within a few minutes to a few hours. The completion of the reaction can be confirmed by visually observing the completion of the precipitation of the reaction product.

[0058] The temperature of the reaction solution is not particularly limited and may be, for example, 5 to 40°C.

[0059] The method for recovering the reaction product as a precipitate is not particularly limited, and the reaction product can be recovered, for example, by decantation or filtration.

[0060] [Cleaning process] By washing the recovered reaction product, water remaining in the reaction product, unreacted quaternary ammonium compound, impurities contained in the conductive polymer aqueous dispersion, and the like can be removed.

[0061] The cleaning liquid is preferably one that can clean the reaction product while minimizing dissolution of the reaction product. Such a cleaning liquid is preferably an organic solvent, more preferably an alcohol-based solvent. The cleaning liquid may contain one type of organic solvent or two or more types of organic solvents.

[0062] The washing method is not particularly limited. For example, a washing liquid may be poured over the reaction product, or the reaction product may be gently stirred in the washing liquid.

[0063] [Drying process] The method for recovering and drying the washed reaction product is not particularly limited, and known powder drying methods such as natural drying, air drying, and heat drying can be applied. It is preferable that the water content of the reaction product obtained after drying is as small as possible, but from a practical standpoint, the water content may be in the range of 10 mass % or less based on the total mass of the dried reaction product.

[0064] [Crushing process] The method for pulverizing the dried reaction product is not particularly limited, and examples thereof include a method of grinding the product in a mortar, a method of grinding the product using a grinder, and the like. Examples of the pulverizer include a homogenizer, a ball mill, a bead mill, a roller mill, a jet mill, and a hammer mill. By adjusting the crushing time and intensity, the average particle size can be made 500 μm or less. By the above method, the desired conductive composite particles can be obtained. EXAMPLES

[0065] (Production Example 1) Production of polystyrene sulfonic acid 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium styrene sulfonate-containing solution, and about 1000ml of the solvent was removed from the polystyrene sulfonic acid-containing solution by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration, and the polystyrene sulfonic acid was washed with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid.

[0066] (Production Example 2) Preparation of conductive polymer aqueous dispersion 14.2 g of 3,4-ethylenedioxythiophene and a solution in which 36.7 g of polystyrene sulfonic acid was dissolved in 2000 ml of ion-exchanged water were mixed at 20°C. The resulting mixed solution was kept at 20° C., and while stirring, 29.64 g of ammonium persulfate and 8.0 g of an oxidation catalyst solution of ferric sulfate dissolved in 200 ml of ion-exchanged water were slowly added, followed by stirring for 3 hours to allow the reaction to proceed. To the reaction solution, 2000 ml of ion-exchanged water was added, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated three times. Next, 200 ml of sulfuric acid diluted to 10% by mass and 2000 ml of ion-exchanged water were added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. 2000 ml of ion-exchanged water was added to the remaining liquid, and about 2000 ml of the solution was removed by ultrafiltration. This operation was repeated three times. Furthermore, 2000 ml of ion-exchanged water was added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated five times to obtain a polystyrene sulfonate-doped poly(3,4-ethylenedioxythiophene) (PEDOT-PSS aqueous dispersion) solution with a concentration of 1.2 mass%. The content of PSS relative to the PEDOT-PSS solid content was 75 mass%.

[0067] Example 1 100g of the PEDOT-PSS aqueous dispersion prepared in Production Example 2 was added dropwise to a reaction solution in which 2.9g of tetrabutylammonium chloride was dissolved in 100g of ethanol, and the mixture was stirred for 30 minutes. As a result, a reaction product of tetrabutylammonium chloride and a conductive complex was precipitated. This precipitate was filtered, and 100g of isopropyl alcohol was added and stirred for 30 minutes while lightly suspending the precipitate. The precipitate was then filtered again, dried at 120°C for 2 hours, and pulverized in a mortar to obtain 1.1g of the desired conductive complex particles. The average particle size was 110μm. 0.1 g of the conductive composite particles was pressed with a commercially available tablet molding machine to obtain a cylindrical tablet (diameter 10 mm, thickness 1.3 mm).

[0068] Example 2 Except for changing 2.9 g of tetrabutylammonium bromide to 2.9 g of tetrabutylammonium chloride, the same procedure as in Example 1 was carried out to obtain 1.1 g of the target conductive composite particles. The average particle size was 120 μm. Using 0.1 g of these conductive composite particles, a cylindrical tablet of the same size as in Example 1 was obtained.

[0069] Example 3 100g of the PEDOT-PSS aqueous dispersion prepared in Production Example 2 was added dropwise to a reaction solution in which 2.9g of tetrabutylammonium bromide was dissolved in 200g of ethanol, and the mixture was stirred for 30 minutes. As a result, a reaction product of tetrabutylammonium bromide and a conductive complex was precipitated. This precipitate was filtered, and 100g of isopropyl alcohol was added and stirred for 30 minutes while lightly suspending the precipitate. The precipitate was then filtered again, dried at 120°C for 2 hours, and pulverized in a mortar to obtain 1.1g of the desired conductive complex particles. The average particle size was 42μm. Using 0.1 g of these conductive composite particles, a cylindrical tablet of the same size as in Example 1 was obtained.

[0070] Example 4 Except for changing 2.9 g of tetrabutylammonium bromide to 2.4 g of tetraoctylammonium bromide, the same procedure as in Example 3 was carried out to obtain 1.1 g of the target conductive composite particles. The average particle size was 35 μm. Using 0.1 g of these conductive composite particles, a cylindrical tablet of the same size as in Example 1 was obtained.

[0071] Example 5 Except for changing 2.9 g of tetrabutylammonium bromide to 2.4 g of tetradecylammonium bromide, the same procedure as in Example 3 was carried out to obtain 1.1 g of the target conductive composite particles. The average particle size was 40 μm. Using 0.1 g of these conductive composite particles, a cylindrical tablet of the same size as in Example 1 was obtained.

[0072] Example 6 The conductive composite particles were filtered in the same manner as in Example 1, and the time for grinding in a mortar was shortened to obtain 1.1 g of the target conductive composite particles. The average particle size was 600 μm. Using 0.1 g of these conductive composite particles, a cylindrical tablet of the same size as in Example 1 was obtained.

[0073] Comparative Example 1 Except for changing 2.9 g of tetrabutylammonium chloride to 5 g of trioctylamine, the same procedure as in Example 1 was carried out to obtain 1.1 g of conductive composite particles. The average particle size was 100 μm. Using 0.1 g of these conductive composite particles, a cylindrical tablet of the same size as in Example 1 was obtained.

[0074] Comparative Example 2 Except for changing 2.9 g of tetrabutylammonium chloride to 5 g of tributylamine, the same procedure as in Example 1 was carried out to obtain 1.1 g of conductive composite particles. The average particle size was 120 μm. Using 0.1 g of these conductive composite particles, a cylindrical tablet of the same size as in Example 1 was obtained.

[0075] [Method of measuring average particle size] In order to measure the average particle size of the conductive composite particles produced in each example, a measurement sample was prepared according to the following procedure. The procedure was as follows: 5 ml of isopropyl alcohol was added to 0.1 g of the pulverized conductive composite particles, one drop of dispersant DISPERBYK-190 (manufactured by BYK Japan) was added, and then ultrasonic dispersion treatment was performed. After that, ion-exchanged water was added to make the volume 20 mL, and ultrasonic dispersion treatment was performed again. This dispersion was placed in a measurement flow cell and measured at a temperature of 20 to 25 ° C using a water circulation system. A commercially available laser diffraction particle size distribution measuring device was used for the measurement.

[0076] [Conductivity measurement] The electrical conductivity (unit: S / cm) of the cylindrical tablets prepared in each example was measured with a PSP probe using Loresta GX (manufactured by Nitto Seiko Analytech Co., Ltd.).

[0077] [Table 1]

[0078] All of the electrodes made of the conductive composite particles of the respective Examples according to the present invention exhibited good electrical conductivity. Comparing Example 1 and Example 2, the average particle diameter is equivalent but the conductivity of Example 1 is superior, which shows that the conductivity is higher when a quaternary ammonium compound having a chloride ion is used than when a quaternary ammonium compound having a bromide ion is used. Comparing Examples 1, 3, and 6, it can be seen that the smaller the average particle size, the higher the electrical conductivity. The electrical conductivity of Example 4 was particularly excellent. Since the average particle sizes of Examples 3 to 5 were similarly small, it can be seen that, from the viewpoint of improving electrical conductivity, the number of carbon atoms in each hydrocarbon group bonded to a nitrogen atom of the quaternary ammonium compound is preferably 12 or less, more preferably 3 to 9, and further preferably 5 to 8. In Comparative Examples 1 and 2, a tertiary amine was reacted instead of a quaternary ammonium compound, and therefore the electrical conductivity was poor.

Claims

1. A conductive composite particle containing a conductive composite including a π-conjugated conductive polymer and a polyanion, wherein a part of an anion group of the polyanion is modified by a reaction with a quaternary ammonium compound (excluding the case of a carbonate of a quaternary ammonium), the four monovalent organic groups bonded to the nitrogen atom of the quaternary ammonium compound are hydrocarbon groups, the four hydrocarbon groups each independently have 4 or more carbon atoms, and the total number of carbon atoms of the four hydrocarbon groups is 16 to 48; The conductive composite particles, wherein the π-conjugated conductive polymer comprises poly(3,4-ethylenedioxythiophene) and the polyanion comprises polystyrenesulfonic acid.

2. The conductive composite particle described in claim 1, wherein the four hydrocarbon groups are aliphatic hydrocarbon groups.

3. The conductive composite particle described in claim 1 or 2, wherein the water content relative to the total mass of the conductive composite particle is 20 mass% or less.

4. The conductive composite particle described in any one of claims 1 to 3, wherein the quaternary ammonium compound includes a quaternary ammonium chloride.

5. The conductive composite particle according to any one of claims 1 to 4, wherein the quaternary ammonium compound comprises at least one selected from the group consisting of tetrabutylammonium, tetraoctylammonium, and tetradecylammonium.

6. The conductive composite particle according to any one of claims 1 to 5, having an average particle size of 35 µm or more and 500 µm or less.

7. An electrode comprising the conductive composite particles according to any one of claims 1 to 6.

8. A reaction solution containing a quaternary ammonium compound (excluding quaternary ammonium carbonates) and an organic solvent, By adding a conductive polymer aqueous dispersion containing a conductive complex containing a π-conjugated conductive polymer and a polyanion, and water, a step of reacting the quaternary ammonium compound with a part of the anion groups of the polyanion of the conductive complex and precipitating a reaction product; washing the reaction product with a washing liquid; drying the washed reaction product; and grinding the dried reaction product to obtain conductive composite particles. the four monovalent organic groups bonded to the nitrogen atom of the quaternary ammonium compound are hydrocarbon groups, the four hydrocarbon groups each independently have 4 or more carbon atoms, and the total number of carbon atoms of the four hydrocarbon groups is 16 to 48; The method for producing conductive composite particles, wherein the π-conjugated conductive polymer contains poly(3,4-ethylenedioxythiophene) and the polyanion contains polystyrenesulfonic acid.

9. A method for producing conductive composite particles as described in claim 8, wherein the four hydrocarbon groups are aliphatic hydrocarbon groups.

10. The method for producing conductive composite particles according to claim 8 or 9, wherein the quaternary ammonium compound comprises a quaternary ammonium halide.

Citation Information

Patent Citations

  • Composition for an antistatic release agent and antistatic release film

    JP2014189597A

  • Method for producing conductive solid matter, method for producing conductive polymer organic solvent dispersion liquid, method for producing antistatic film and antistatic film

    JP2016169255A

  • Method for producing amine adduct of conductive composite, method for producing amine adduct liquid of conductive composite and method for producing conductive film

    JP2018053191A

  • Conductive polymer composition, conductive polymer film, and electrolytic capacitor

    JP2019192752A

  • Conductive particle and method for producing the same, conductive polymer-containing liquid, electrode, and method for producing conductive film

    JP2020107413A